The second wave of desaturation in coronavirus disease 2019 - M.I. Alghizzawi (17280592) (2021)
After a complete symptomatic recovery from coronavirus disease 2019 pneumonia, the second phase of desaturation is a new phenomenon that is being increasingly observed. Two possible mechanisms behind it can be a continued subclinical infection and lung fibrosis. We have presented a case with the former mechanism, who responded well to steroids. Other Information Published in: New Microbes and New Infections License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.nmni.2021.100866